2019
DOI: 10.1080/03019233.2019.1589755
|View full text |Cite
|
Sign up to set email alerts
|

Review and data evaluation for high-temperature reduction of iron oxide particles in suspension

Abstract: High-temperature reduction processes of iron oxide particles suspension are promising in carbon emission abatement. Recently, researchers have contributed abundant knowledge of the reaction mechanism and kinetics of iron oxide particles above 1473 K, while there was very limited information 10 years ago. Although the understanding of the high-temperature reduction of iron oxide particles is still not comprehensive, a brief review of the academic reports is helpful for the future work on this topic. The high-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…According to the observed mass losses (see Table 2 ), these processes can be assigned to the transformation of γ-Fe 2 O 3 to Fe 3 O 4 and to the reduction of Fe 3 O 4 to metallic Fe, respectively. It is worth noting the low temperature at which Fe 3 O 4 reduces to metallic Fe which usually occurs at higher temperatures (T > 900 °C) [ 45 , 46 ]. This is because the nanoparticles have a large specific surface exposed to H 2 gas which favors the reduction.…”
Section: Resultsmentioning
confidence: 99%
“…According to the observed mass losses (see Table 2 ), these processes can be assigned to the transformation of γ-Fe 2 O 3 to Fe 3 O 4 and to the reduction of Fe 3 O 4 to metallic Fe, respectively. It is worth noting the low temperature at which Fe 3 O 4 reduces to metallic Fe which usually occurs at higher temperatures (T > 900 °C) [ 45 , 46 ]. This is because the nanoparticles have a large specific surface exposed to H 2 gas which favors the reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Hematite ore was partially reduced to suboxides in the specified atmospheres. Accorading to the thermodynamic analysis, [14,15] these suboxides contained magnetite and liquid oxide, and the liquid oxide turned to wu¨stite in the quenching process. The partially reduced ore particles in resin were polished and investigated with an optical microscope.…”
Section: A Morphology and Compositionmentioning
confidence: 99%
“…Several reactions take place simultaneously during rapid heating of the carbonaceous materials, including break-up of chemical bonds, vaporization, and condensation [50]. Previous studies have indicated that the post combustion ratio (PCR) value of reducing gas has an important influence on the pre-reduction degree in the HIsarna's cyclone, which is greatly influenced by carbonaceous materials devolatilization [17], [51]. The total yield of gas products evolved from the carbon sources (per 1 gram of sample) during rapid heating to the temperatures of 1500 °C is plotted in Figure 9.…”
Section: Comparison Of Rapid Devolatilisation Behaviours For Differen...mentioning
confidence: 99%